Manejo e caracterização dos dejetos compostados da bovinocultura de leite e sua contribuição ambiental - Zulpo, Maikielli (2020)
Dairy cattle farming stands out among agricultural activities in Brazil and Rio Grande do Sul, a reference on the national scene as one of the largest milk producers. The activity is characterized by the production of large quantities of manure, urine and effluents, resulting from the operation and cleaning of the facilities, which, when handled poorly, can cause environmental pollution. The study aimed in the first chapter to carry out a historical survey on dairy cattle in Brazil, emphasizing the state of Rio Grande do Sul, by consulting studies published in the area, evaluating how Brazilian environmental legislation and that of Rio Grande do Sul regulate the activity. In the second chapter we seek to characterize the physical attributes of the organic compost, obtained from the composting of bovine manure, evaluated in four rearing systems (organic system, semi-confined, Free stall and compost barn), the use of efficient microorganisms (EM) was evaluated during the composting process. The experiment was carried out in a randomized block design, for a period of 60 days, with the manual turning of the reactor contents. The MS was added fortnightly (4X) at a dose of 150 ml per reactor. The attributes Density, Density of solids, Total Porosity, Porosity of aeration, Available water, Average geometric diameter, Organic Carbon, pH in water and pH in CaCl2 were measured. The results of the studies show that the use of MS did not influence the physical attributes of organic compost from cattle manure, however its use provides biological quality to the system where the products activated by them will be inserted. The organic compost obtained was excellent for the formulation of substrates and as a soil conditioner. It is advisable to study the biological composition of the compounds produced in the future. The use of manure produced in rural properties and environmental licensing, provide for the adequacy of facilities, added to good management practices, giving greater sustainability to rural properties and family farming.